Pertumbuhan Bibit F0 Jamur Tiram Dan Jamur Merang Pada Media Ubi Jalar Ungu - Muyasarah, Fatimah, Dra. Suparti. M.Si (2017)
Tubers is one food that has a high carbohydrate content that can be used as a substitute for potatoes in the manufacture of seeds F0 mushrooms. Purple sweet potato can be used as growth medium of F0 oyster mushroom and straw mushroom in various variety of treatment that is extract, porridge or flour. The purpose of this study to determine the color, thickness and growth rate of mycelium seeds F0 oyster mushrooms and straw mushrooms. This study used a complete randomized design (RAL) with two factorials. The first factor is the treatment of purple sweet potato media, while the second factor is the type of fungus. The results showed that the speed of growth of mycelium seeds of F0 for the fastest oyster mushroom was on extract medium (M1J1) which was 3.9 cm and the latter was flour medium (M3J1) that was 2.0 cm. While the growth speed of mycelium seeds of F0 mushroom is the fastest in the flour medium (M3J2) which is 4.5 cm and the late is extract medium (M1J2) that is 0.8 cm. Mycelium seeds F0 Oysters are compact and thick white oyster, while white fungus is not compact but also thick. Keywords : Media extract, porridge and purple sweet potato flour, Oystermushroom, Mushroom,seeds F0